Two DNA Methyltransferases for Site-Specific 6mA and 5mC DNA Modification in Xanthomonas euvesicatoria - Park, Hye-Jee; Seong, Hoon Je; Lee, Jongchan; Heo, Lynn; Sul, Woo Jun; Han, Sang-Wook (Frontiers in Plant Science, 2021)
Xanthomonas euvesicatoria (Xe) is a gram-negative phytopathogenic bacterium that causes bacterial spot disease in tomato/pepper leading to economic losses in plantations. DNA methyltransferases (MTases) are critical for the survival of prokaryotes; however, their functions in phytopathogenic bacteria remain unclear. In this study, we characterized the functions of two putative DNA MTases, XvDMT1 and XvDMT2, in Xe by generating XvDMT1- and XvDMT2-overexpressing strains, Xe(XvDMT1) and Xe(XvDMT2), respectively. Virulence of Xe(XvDMT2), but not Xe(XvDMT1), on tomato was dramatically reduced. To postulate the biological processes involving XvDMTs, we performed a label-free shotgun comparative proteomic analysis, and results suggest that XvDMT1 and XvDMT2 have distinct roles in Xe. We further characterized the functions of XvDMTs using diverse phenotypic assays. Notably, both Xe(XvDMT1) and Xe(XvDMT2) showed growth retardation in the presence of sucrose and fructose as the sole carbon source, with Xe(XvDMT2) being the most severely affected. In addition, biofilm formation and production of exopolysaccharides were declined in Xe(XvDMT2), but not Xe(XvDMT1). Xe(XvDMT2) was more tolerant to EtOH than Xe(XvDMT1), which had enhanced tolerance to sorbitol but decreased tolerance to polymyxin B. Using single-molecule real-time sequencing and methylation-sensitive restriction enzymes, we successfully predicted putative motifs methylated by XvDMT1 and XvDMT2, which are previously uncharacterized 6mA and 5mC DNA MTases, respectively. This study provided new insights into the biological functions of DNA MTases in prokaryotic organisms.